In-plane and out-of-plane needle insertion comparison for a novel lateral block of the radial, ulnar, median and musculocutaneous nerves in cats. (July 2019) - Leung, Jessica B.Y.; Rodrigo-Mocholi, Diego; Martinez-Taboada, Fernando
Abstract: Objective: To compare two needle insertion techniques in a novel lateral approach to the radial, ulnar, median and musculocutaneous (RUMM) nerve block in cat cadavers. Study design: Prospective, cadaveric experimental study. Animals: A group of 18 feline cadavers. Methods: Cadavers were divided into two groups. Both thoracic limbs of each cat were 'blocked' using the 'in-plane' (IP) or 'out-of-plane' (OP) ultrasound (US)-guided method. A single operator with limited experience performed all the techniques. Cadavers were placed in lateral recumbency and the uppermost limb was injected before turning to 'block' the contralateral limb in the same manner. The IP method consisted of tracking the triceps brachii muscle until the radial (R) nerve could be identified in the same field of view as the ulnar, median and musculocutaneous (UMM) nerve bundle. A needle was guided by US towards the R nerve and subsequently, methylene blue (0.4 mL) was instilled adjacent to it. The needle was retracted and redirected to the UMM nerve bundle, and another 0.4 mL dye was instilled. For the OP technique, the limb was pronated at a 45° angle. The nerves were then identified with the R nerve directly above UMM nerves. A needle was directed OP deep towards UMM nerves and dye (0.4 mL) was instilled. The needle was retracted superficially and 0.4 mL dye instilled next to the R nerve. After dissection, the nerves were assessed and ≥6 mm of staining was considered a successful technique. Results: A total of 18 RUMM 'blocks' were performed IP and 18 were performed OP. The IP technique was more successful than the OP technique (R nerve p = 0.0339; UMM nerves p = 0.0352). Conclusions and clinical relevance: The lateral approach to the RUMM was achievable in cat cadavers using both needle insertion techniques. The IP technique was significantly more successful than the OP technique.